Pemanfaatan Sistim Informasi Geografi Untuk Analisis Jarak Jangkauan Pelayanan Fasilitas Kesehatan di Kota Ambon - Abdul Muin; Heinrich Rakuasa (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Ambon City is the most populous city in Maluku, and accessibility is one of the main challenges in meeting health service needs. To overcome this problem, it is necessary to conduct an in-depth analysis of the distance of health facility services in Ambon City.  This study uses a spatial analysis method to map the location and distance between major health facilities such as hospitals, health centers, and clinics throughout Ambon City. The results show that there are diverse spatial patterns in the coverage of health facilities in Ambon City. The spatial pattern of health facility coverage in Ambon City is classified into 5 classes, namely very close covering 7,586, 42 ha, close covering 10,172, 23 ha, medium covering 3,697, 07 ha, far covering 3,473.59 ha and very far covering 7,644, 36 ha. The results of this study also show that Teluk Ambon sub-district has a very large percentage of area at the very close, close and very far reach levels of health facilities compared to other sub-districts in Ambon City, while the area at the medium and far reach levels is dominated by Nusaniwe sub-district which has a larger percentage of area than other sub-districts. This study makes an important contribution to understanding the spatial pattern of health facility coverage in Ambon City and provides a basis for spatially-based decision-making.